FPR1 blockade prevents receptor regulation by mitochondrial DAMPs and preserves neutrophil function after trauma - Itagaki, Kiyoshi (Crit Care Med, 2020)
OBJECTIVES: Trauma predisposes to systemic sterile inflammation (SIRS) as well as infection, but the mechanisms linking injury to infection are poorly understood. Mitochondrial debris (MTD) contains formyl peptides (mtFPs). These bind formyl peptide receptor-1 (FPR1), trafficking neutrophils (PMN) to wounds, initiating SIRS and wound healing. Bacterial FPs (bFPs) however, also attract PMN via FPR1. Thus mtFPs might suppress PMN antimicrobial function. Also, FPR1 blockade used to mitigate SIRS might predispose to sepsis. We examined how mtFPs impact PMN functions contributing to antimicrobial responses, and how FPR1 antagonists affect those functions. DESIGN: Prospective study of human and murine PMN and clinical cohort analysis. SETTING: University research laboratory and Level 1 trauma center. PATIENTS: Trauma patients, volunteer controls. ANIMAL SUBJECTS: C57Bl/6, FPR1, and FPR2 knockout mice. INTERVENTIONS: Human and murine PMN functions were activated with autologous MTD, mtFPs or bFPs followed by chemokines or leukotrienes. The experiments were repeated using FPR1 antagonist cyclosporin H (CsH), ‘designer’ human FPR1 antagonists (POL7178 and POL7200) or anti-FPR1 antibodies. Mouse injury/lung infection model was used to evaluate effect of FPR1 inhibition. MEASUREMENTS AND MAIN RESULTS: Human PMN cytosolic calcium, chemotaxis, reactive oxygen species (ROS) production and phagocytosis were studied before and after exposure to MTD, mtFPs and bFPs. mtFP and bFPs had similar effects on PMN. Responses to chemokines and leukotrienes were suppressed by prior exposure to FPs. POL7200 and POL7178 were specific antagonists of human FPR1 and more effective than CsH or anti-FPR1 antibodies. FPs inhibited mouse PMN responses to chemokines only if FPR1 was present. FPR1 blockade did not inhibit PMN bacterial phagocytosis or ROS production. CsH increased bacterial clearance in lungs after injury. CONCLUSIONS: FPs both activate and desensitize PMN. FPR1 blockade prevents desensitization, potentially both diminishing SIRS and protecting the host against secondary infection after tissue trauma or primary infection.